'Tell Them Our Story': Memories of the Sumi Naga Labour Corps in World War I. Issue 1 (2nd January 2023) - Achumi, Ilito H.
Abstract: This article recounts the ways in which the Sumi (or Sema) Naga tribes of Northeast India remember their service in Europe during World War I (1914–18). The state records pertaining to the Sumi Naga Labour Corps (SNLC) in the War were destroyed during the Japanese invasion of Kohima in 1944. However, the descendants of the SNLC members have transmitted and preserved their experiences through oral histories and storytelling, leaving a vast repository of cultural histories that weave together structures of wars, politics, violence, and ideas of nations. The article delves into the personal experiences evident in these memories and critiques the silencing of non-literary communities where they find no resonance with written archives, demonstrating that storytelling is pivotal in the transmission of ideas and the prosecution of wars. The scarcity and fragility of Naga memories of events beyond Nagaland raise questions about the relationship between oral and written history.